2020
DOI: 10.1021/acs.energyfuels.0c01200
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning and Emission Characteristics of Hg, Cr, Pb, and As Among Air Pollution Control Devices in Chinese Coal-Fired Industrial Boilers

Abstract: Toxic trace elements (TEs), such as Hg, Cr, As, and Pb, emitted from coal-fired industrial boilers (CFIBs) have gained considerable attention because of their harmful effects on environmental quality and human health. In this study, based on the field test data, Hg, Cr, Pb, and As emissions from six CFIBs in China were investigated. Solid samples including feed coal, bottom ash, fly ash, and gypsum, desulfurization wastewater samples, and stack flue gas samples were simultaneously collected for determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…1 : where is the discharge of the j th air pollutant generated by the sector i , is the emission factor of the j th air pollutant from the combustion of the k th type of fuel source in sector i , is the total amount of the k th type of fuel consumed by the sector i , is the emission factor of the j th air pollutant for the industrial process of producing product k , is the total amount of k produced by the sector i , and n is the number of products from sector i which varies across sectors. Data for and are from the Intergovernmental Panel on Climate Change (IPCC) 22 – 24 , the Ministry of Ecology and Environment of the People’s Republic of China (MEEPRC) 25 , 26 , and previous studies 27 33 . Besides, the sector of Electricity & Heat Production and Supply also consumes fuel sources in their energy conversion process.…”
Section: Methodsmentioning
confidence: 99%
“…1 : where is the discharge of the j th air pollutant generated by the sector i , is the emission factor of the j th air pollutant from the combustion of the k th type of fuel source in sector i , is the total amount of the k th type of fuel consumed by the sector i , is the emission factor of the j th air pollutant for the industrial process of producing product k , is the total amount of k produced by the sector i , and n is the number of products from sector i which varies across sectors. Data for and are from the Intergovernmental Panel on Climate Change (IPCC) 22 – 24 , the Ministry of Ecology and Environment of the People’s Republic of China (MEEPRC) 25 , 26 , and previous studies 27 33 . Besides, the sector of Electricity & Heat Production and Supply also consumes fuel sources in their energy conversion process.…”
Section: Methodsmentioning
confidence: 99%
“…Heavy metal pollution is closely related to the regional economic development level and the nature of leading local enterprises. In particular, regional soil pollution due to heavy metal is more serious with a higher degree of industrialization, such as the combustion of coal, oil, and other traditional energy minerals and the "three waste" emissions of chemical mining, mainly enriching the soil layer with As, Cd, Cr, Hg, Pb, Cu, and Zn elements [19,20]. Peng et al [8] showed that the content of heavy metals in soil was relatively high in the Chinese cities of economically developed coastal provinces (e.g., Zhejiang) and resource-based provinces (e.g., Hunan).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, many gaseous pollutants control technologies have been developed. In these technologies, wet flue gas desulfurization (WFGD) and selective catalytic reduction (SCR) denitration are the two most widely used SO 2 and NO x removal technologies. Activated carbon adsorption is the main removal technology of heavy metals, Hg and As, from gas stream. Alcohol amine absorption and catalytic oxidation are the most widely used treatment technologies of gaseous H 2 S. The mainstream removal technologies of VOCs are rich due to huge types of VOCs and their different characteristics. Adsorption, absorption, condensation, and catalytic combustion are the common VOCs removal technologies. Supporting Information (SI) Figure S1 shows the classification of these gaseous pollutants common removal technologies.…”
Section: Introductionmentioning
confidence: 99%